Prinsip-Prinsip Keluarga Kristen Sebagai Pusat Pendidikan Menurut Ulangan 6:1-25 - Paulus Kunto Baskoro (Sekolah Tinggi Theologia Nazarene Indonesia, 2021)
ABSTRACT Whether or not the dynamics of family life are destroyed is determined by the education in the family itself. Especially education in a Christian family or the principles of education in a family of believers. Several reasons are the background of this writing problem. First, there is the unconsciousness of some family of believers about the importance of the family as the center of teaching. Second, there are some couples or families of believers who are too busy with outside work rather than taking care of family life. Third, many Christian families today only focus on making ends meet. Fourth, many Christian families are currently experiencing problems regarding the impact of families with worldly life. With this method the author studies Deuteronomy 6: 1-25 as a whole, then adds from other books on the principles of pastoral care. This research uses descriptive method, namely studying the principles of the Christian family as a teaching center according to Deuteronomy 6: 1-25 which is a special revelation. Which finally has a big goal, First, for every family of believers to realize how important the family is as the center of teaching. Second, it is hoped that every family of believers can understand each other and encourage family after family. Third, the most essential thing is that every family of believers can become a figure or role model in the focus of the family being the center of teaching.